1989
DOI: 10.1128/aac.33.5.663
|View full text |Cite
|
Sign up to set email alerts
|

Combinations of 3'-azido-3'-deoxythymidine (zidovudine) and phosphonoformate (foscarnet) against human immunodeficiency virus type 1 and cytomegalovirus replication in vitro

Abstract: Combinations of 3'-azido-3'-deoxythymidine and phosphonoformate produced a moderate synergistic inhibitory effect against human immunodeficiency virus type 1 in vitro at concentrations that are easily achieved in humans. The synergistic effect was more pronounced with increasing concentrations and was not secondary to toxic effects of the drugs. 3'-Azido-3'-deoxythymidine neither inhibited the replication of human cytomegalovirus in human embryonic lung fibroblasts nor interfered with the anticytomegalovirus e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
36
0

Year Published

1990
1990
2006
2006

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(38 citation statements)
references
References 41 publications
2
36
0
Order By: Relevance
“…On structural grounds, the site of interaction for PP i (and, presumably, for foscarnet) should lie within the deoxynucleoside triphosphate (dNTP) binding site since PP i is formed from the ␤ and ␥ phosphates of the dNTP substrate, but foscarnet inhibition of DNA synthesis in vitro is noncompetitive with dNTP substrates (58), indicating that foscarnet and dNTP bind to distinguishable forms of RT. In addition, median-effect analysis comparing foscarnet and 3Ј-azido-3Ј-deoxythymidine (AZT) triphosphate (AZTTP) alone or as mixtures has shown that inhibition by these compounds is mutually exclusive (10, 22, 50), implying that binding of either inhibitor prevents binding of the other to the same enzyme molecule.In intact cells, the inhibition of HIV-1 by foscarnet and AZT is synergistic (10,22). The mechanism of this synergy is unclear, but it has recently been demonstrated that AZT monophosphate (AZTMP) incorporation can be reversed by the primer-unblocking activity of RT, in which the chain-terminating residue is transferred to an acceptor substrate such as PP i or an NDP or NTP (1, 4, 32, 34).…”
mentioning
confidence: 99%
“…On structural grounds, the site of interaction for PP i (and, presumably, for foscarnet) should lie within the deoxynucleoside triphosphate (dNTP) binding site since PP i is formed from the ␤ and ␥ phosphates of the dNTP substrate, but foscarnet inhibition of DNA synthesis in vitro is noncompetitive with dNTP substrates (58), indicating that foscarnet and dNTP bind to distinguishable forms of RT. In addition, median-effect analysis comparing foscarnet and 3Ј-azido-3Ј-deoxythymidine (AZT) triphosphate (AZTTP) alone or as mixtures has shown that inhibition by these compounds is mutually exclusive (10, 22, 50), implying that binding of either inhibitor prevents binding of the other to the same enzyme molecule.In intact cells, the inhibition of HIV-1 by foscarnet and AZT is synergistic (10,22). The mechanism of this synergy is unclear, but it has recently been demonstrated that AZT monophosphate (AZTMP) incorporation can be reversed by the primer-unblocking activity of RT, in which the chain-terminating residue is transferred to an acceptor substrate such as PP i or an NDP or NTP (1, 4, 32, 34).…”
mentioning
confidence: 99%
“…Furthermore, administration of both GCV and AZT to CMV-infected AIDS patients in clinical trials has revealed the increased toxicity of this combination (Jacobson et ei., 1988b;Hochster et al, 1990;Millar et el., 1990; Studies of ocular complications of AIDS research group, 1992). Conversely, the combination of PFA and AZT synergistically inhibits HIV replication in vitro (Eriksson and Schinazi, 1989;Koshida et el., 1989;Kong et et., 1991). A clinical trial comparing GCV and PFA for treatment of CMV retinitis in AIDS patients showed PFA to have a survival benefit over GCV, even after correction for the length of anti-retroviral therapy (Studies of ocular complications of AIDS research group, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…In vitro data suggest that the inhibition of HIV replication by foscamet and zidovudine is synergistic [1,2]. In our study, it is interesting that the 2 patients receiving zidovudine during foscamet treatment had the largest decrease in HIV viremia (-1.49 and -1.53 log RNA/mL).…”
Section: Discussionmentioning
confidence: 52%
“…Foscamet (sodium salt of phosphonoformic acid) is, in vitro, a noncompetitive inhibitor of human immunodeficiency virus (HIV) reverse transcriptase and decreases HIV replication [1,2]. In AIDS patients treated with foscamet for cytomegalovirus (CMV) retinitis, a decrease in p24 antigenemia was observed, suggesting an inhibition of HIV replication in vivo [3,4].…”
mentioning
confidence: 99%